Two-Handed Spatial Interface Tools for Neurosurgical Planning - Hinckley, Ken; Goble, John C.; Pausch, Randy; Snell, John W.; Kassell, Neal F. (Computer, 1995)
The authors' computer-based neurosurgical planning system, Netra, incorporates a 3D user interface based on the two-handed physical manipulation of handheld tools in free space. These user-interface props help transfer the neurosurgeon's skills for manipulating tools to operating a user interface for visualizing 3D medical images. From the surgeon's perspective, the interface is analogous to holding a miniature head in one hand. This head can be "sliced open" or pointed to via a cross-sectioning plane or a stylus tool, respectively, held in the other hand. The authors' informal evaluations of over 50 neurosurgeons have shown that with a cursory introduction, surgeons can understand and use the interface within about one minute of touching the props. The system is intended for clinical use by neurosurgeons doing real work. The authors have tested it in the context of surgical procedures involving real patients. In fact, various components of Netra have been used for approximately 40 patients in clinical cases involving epilepsy, brain tumors, or neurological-based motor disorders. Initial experiences indicate that technology-based systems such as Netra can significantly contribute to the surgical management of patients with certain neurological diseases.